2021
DOI: 10.1161/jaha.120.018013
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Prediction Model for Stroke, Cardiac, and Mortality Risk After Non‐Cardiac Surgery

Abstract: Background Commonly used cardiovascular risk calculators do not provide risk estimation of stroke, a major postoperative complication with high morbidity and mortality. We developed and validated an accurate cardiovascular risk prediction tool for stroke, major cardiac complications (myocardial infarction or cardiac arrest), and mortality after non‐cardiac surgery. Methods and Results This retrospective cohort study included 1 165 750 surgical patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
2
18
0
3
Order By: Relevance
“…Of the entire patient cohort, 237 (0.58%) experienced an ischemic stroke within 30 days after surgery. The stroke incidence was consistent with previously reported rates of 0.1–0.7% in patients who underwent non-cardiac surgery ( Vasivej et al, 2016 ; Woo et al, 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…Of the entire patient cohort, 237 (0.58%) experienced an ischemic stroke within 30 days after surgery. The stroke incidence was consistent with previously reported rates of 0.1–0.7% in patients who underwent non-cardiac surgery ( Vasivej et al, 2016 ; Woo et al, 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…In the PeriOpearative Ischemic Evaluation (POISE) trial of 8,351 patients who underwent non-cardiac surgery, 60 (0.7%) patients developed stroke within 30 days after surgery ( POISE Study Group et al, 2008 ). A recent retrospective cohort study, such as 1,165,750 surgical patients, suggests that postoperative ischemic stroke was found in 2,500 patients (0.25%) ( Woo et al, 2021 ). In the current study, 484 patients with postoperative ischemic stroke were found in a large cohort of 2,21,541 patients with non-cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There is even less data here. For example, the lifetime risk of ESRD after LDN in a 70-year-old man is 0.15% (95% CI 0.05, 0.28), and the relative risk for ESRD from non-insulin dependent diabetes is 3.01 (1.91, 4.74)- the absolute risk would appear to be low, but we have no data on the effect of donation on subsequent ESRD in this scenario ( 22 ).…”
Section: Risk Benefit Balancementioning
confidence: 94%